Separation of Phycobiliprotein from Nostoc Commune by Using Ion-Exchange Membrane with Quaternary Amine. Issue 1 (2nd January 2023) - Hidane, Takanori; Fukui, Tomohiro; Demura, Mikihide; Morisada, Shintaro; Ohto, Keisuke; Kawakita, Hidetaka
ABSTRACT: Phycobiliprotein (PB), which is produced by cyanobacteria, has potential applications as a valuable pharmaceutical product. In this study, PB was separated by using a nonwoven-fabric membrane (Rx-1) that contained quaternary amino groups. PB was extracted from a Nostoc commune, which is a type of microalga, by disrupting the cell walls by a freeze–thaw method. Two types of biomolecules, namely PB and other biomolecules X, were identified by gel permeation chromatography. Permeation of the PB-containing solution through Rx-1 increased the purity of the PB in the filtrate from 0.25 to 0.45. The adsorption constant ( K p ) and maximum adsorbed amount of each protein on Rx-1 ( q max ) were determined by fitting the experimental data to a mathematical model. The obtained values for K p and q max were used to simulate scaled-up treatment of a PB-containing solution. Permeation of a PB-containing solution (3.0 L at 1.2 × 10 −3 m 3 /h) through Rx-1 (volume of scale-up membrane, 8.0 × 10 −4 m 3 ) enabled PB separation for 26 h. Further PB purification could be achieved by using the Rx-1 membrane in combination with precipitation with ammonium sulfate solution and an ultrafiltration membrane.